2012
DOI: 10.1371/journal.pone.0032633
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Organization, Tissue Distribution and Functional Characterization of the Rat Pate Gene Cluster

Abstract: The cysteine rich p rostate a nd t estis e xpressed ( Pate ) proteins identified till date are thought to resemble the three fingered protein/urokinase-type plasminogen activator receptor proteins. In this study, for the first time, we report the identification, cloning and characterization of rat Pate gene cluster and also determine the expression pattern. The rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
(67 reference statements)
0
13
0
Order By: Relevance
“…Although the Pate genes were initially thought to be prostate-and testisspecific, a recent study indicated their expression in the epididymis and not in the testis and prostate (Turunen et al, 2011). We reported that the rat Pate genes were found to be expressed in the seminal vesicle and epididymis and in tissues beyond the male reproductive tract; and their expression seems to be androgen-dependent (Rajesh and Yenugu, 2012). A characteristic feature of the PATE proteins is the presence of 10 cysteine residues that form two motifs: ( (Fig.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…Although the Pate genes were initially thought to be prostate-and testisspecific, a recent study indicated their expression in the epididymis and not in the testis and prostate (Turunen et al, 2011). We reported that the rat Pate genes were found to be expressed in the seminal vesicle and epididymis and in tissues beyond the male reproductive tract; and their expression seems to be androgen-dependent (Rajesh and Yenugu, 2012). A characteristic feature of the PATE proteins is the presence of 10 cysteine residues that form two motifs: ( (Fig.…”
Section: Introductionmentioning
confidence: 87%
“…Rat PATE and PATE-F antibodies were raised in rabbits as described earlier (Rajesh and Yenugu, 2012). For the initial immunization, rabbits were administered 100 g of recombinant PATE or PATE-F protein mixed with complete adjuvant.…”
Section: Antibody Productionmentioning
confidence: 99%
See 3 more Smart Citations